2021
DOI: 10.3390/ijerph182312390
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Confocal Laser Endomicroscopy for the Diagnosis of Oral Squamous Cell Carcinoma: A Systematic Review and Meta-Analysis

Abstract: Background: Advances in treatment approaches for patients with oral squamous cell carcinoma (OSCC) have been unsuccessful in preventing frequent recurrences and distant metastases, leading to a poor prognosis. Early detection and prevention enable an improved 5-year survival and better prognosis. Confocal Laser Endomicroscopy (CLE) is a non-invasive imaging instrument that could enable an earlier diagnosis and possibly help in reducing unnecessary invasive surgical procedures. Objective: To present an up to da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
(90 reference statements)
1
4
0
2
Order By: Relevance
“…CLE allows for the in vivo visualization of cellular and subcellular structures on the epithelial and subepithelial surface of the anterior human oropharyngeal region with high resolution and frame rates, using acriflavine topically and fluorescein intravenously [ 122 ]. Several studies have demonstrated promising results, including a scoring system to classify benign and malignant tissue in the oral cavity, and an exceptionally high sensitivity and specificity [ 123 , 124 , 125 ]. Another study suggested that CLE may supplant or reduce the need for physical tissue biopsy in the management of oral cancer [ 126 ].…”
Section: Spectroscopy For the Intraoperative Assessment Of The Resect...mentioning
confidence: 99%
“…CLE allows for the in vivo visualization of cellular and subcellular structures on the epithelial and subepithelial surface of the anterior human oropharyngeal region with high resolution and frame rates, using acriflavine topically and fluorescein intravenously [ 122 ]. Several studies have demonstrated promising results, including a scoring system to classify benign and malignant tissue in the oral cavity, and an exceptionally high sensitivity and specificity [ 123 , 124 , 125 ]. Another study suggested that CLE may supplant or reduce the need for physical tissue biopsy in the management of oral cancer [ 126 ].…”
Section: Spectroscopy For the Intraoperative Assessment Of The Resect...mentioning
confidence: 99%
“…Furthermore, OSSC has shown a high recurrence rate (up to 50%) leading to OSCC progression and patients eventually die of tumor recurrence and subsequent metastasis (5,6). OSCC is closely related to environmental factors including tobacco consumption, alcohol habits, nutrition, and viral infections (5,7,8). Of these factors, cigarette smoke is associated with is 7-10 times higher OSCC development when compared to non-smokers (5,8).…”
Section: Introductionmentioning
confidence: 99%
“…OSCC is closely related to environmental factors including tobacco consumption, alcohol habits, nutrition, and viral infections (5,7,8). Of these factors, cigarette smoke is associated with is 7-10 times higher OSCC development when compared to non-smokers (5,8). Despite concerted social efforts to reduce smoking prevalence, current trends suggest that smoking numbers will continue to increase.…”
Section: Introductionmentioning
confidence: 99%
“…46 artigos incluídos nesta revisão guarda-chuva, 17 não relataram o uso de ferramentas para avaliação do risco de viés dos estudos primários revisados(68, 69, 72-75, 79, 81, 82, 85, 88, 93, 96, 99, 101, 107) Outros 3 artigos relataram o uso de escalas/ critérios próprios(76,95,106), o que pode prejudicar a reprodutibilidade e não é aconselhável uma vez que existem ferramentas testadas e publicadas com embasar a presente revisão guarda-chuva(37,70, 71,76,78,80,83,89,92,94,98,102,103,105,106,108).É muito debatido na literatura se existe uma correlação entre a qualidade de um artigo e o fator de impacto da revista (FI) em que ele está publicado. O FI é um indicador calculado anualmente pela base de dados Web of Science, sendo uma ferramenta quantitativa para classificar, avaliar, categorizar e comparar periódicos de mesma área.…”
unclassified
“…Concluiu-se que a baixa quantidade de estudos existentes no continente e a falta de estudos do tipo ECR não permitem validar a Novas tecnologias, utilizadas com maior frequência em outros órgãos, também vem sendo testadas para lesões de boca. O artigo de Sethi et al(102) analisou a acurácia da endomicroscopia confocal a laser no diagnóstico de CEB, uma técnica mais comumente empregada para neoplasias gástricas que utiliza um corante fluorescente e uma sonda microscópica para avaliação do tecido em tempo real.Embora se observe viés e heterogeneidade, este estudo afirma que a endomicroscopia confocal a laser pode ter uma influência clínica notável no diagnóstico de CEB, por meio de sua alta sensibilidade e especificidade, que apresentaram valores de 95% e 93% respectivamente. Entretanto, devido aos custos envolvidos na compra dos equipamentos e capacitação técnica, a endomicroscopia confocal a laser tende a apresentar menor custo-benefício para aplicação durante o rastreamento de lesões, sendo mais promissora para definição de margens de segurança no transcirúrgico.O uso da Inteligência Artificial vem sendo cada vez mais comum na área da saúde, buscando aprimorar o diagnóstico de condições através de técnicas de Telessaúde.…”
unclassified